Microenvironment-derived regulation of HIF signaling drives transcriptional heterogeneity in glioblastoma multiforme - Heiland, Dieter Henrik; Gaebelein, Annette; Börries, Melanie; Wörner, Jakob; Pompe, Nils; Franco, Pamela; Heynckes, Sabrina; Bartholomae, Mark; HAilín, Darren; Carro, Maria Stella; Prinz, Marco; Weber, Stefan; et al. (Molecular Cancer Research, 2018)
The evolving and highly heterogeneous nature of malignant brain tumors underlies their limited response to therapy and poor prognosis. In addition to genetic alterations, highly dynamic processes, such as transcriptional and metabolic reprogramming, play an important role in the development of tumor heterogeneity. The current study reports an adaptive mechanism in which the metabolic environment of malignant glioma drives transcriptional reprogramming. Multiregional analysis of a glioblastoma patient biopsy revealed a metabolic landscape marked by varying stages of hypoxia and creatine enrichment. Creatine treatment and metabolism was further shown to promote a synergistic effect through upregulation of the glycine cleavage system and chemical regulation of prolyl-hydroxylase domain. Consequently, creatine maintained a reduction of reactive oxygen species and change of the a-ketoglutarate/succinate ratio, leading to an inhibition of HIF signaling in primary tumor cell lines. These effects shifted the transcriptional pattern toward a proneural subtype and reduced the rate of cell migration and invasion in vitro. Implications: Transcriptional subclasses of glioblastoma multiforme are heterogeneously distributed within the same tumor. This study uncovered a regulatory function of the tumor microenvironment by metabolism-driven transcriptional reprogramming in infiltrating glioma cells. Mol Cancer Res; 16(4); 655-68
CRIS-Team Scopus Importer:2023-09-13